Konsep Kesabaran dalam Menuntut Ilmu: Analisis Q.S. Al-Kahfi ayat 65-70 - Difani Nur Azizah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The process of seeking knowledge does not merely involve intellectual intelligence but also requires emotional and spiritual strength, one of which is cultivated through patience. In fact, in today's fast-paced, instant era, many knowledge seekers often overlook the aspect of patience. Therefore, this research aims to explore the meaning and urgency of patience in seeking knowledge based on Q.S. Al-Kahfi verses 65-70, which focus on the story of Prophet Musa and Khidr. The method used in this research is a literature review with a qualitative approach, analyzing the relevant verses as well as classical and contemporary interpretations that serve as primary sources. The analysis of this article demonstrates that patience in seeking knowledge is a prerequisite for attaining true knowledge, functioning as an inner strength to overcome obstacles, maintain consistency in learning, and shape the character of a genuine learner who is not only intellectually intelligent but also spiritually mature. These findings are relevant to the integration of manners, ethics, and spirituality in contemporary Islamic education.